The explanatory coexistence of scientific and supernatural explanations: A meta-analysis - Pnevmatikos, Dimitris; Georgiadou, Triantafyllia (Psychology: the Journal of the Hellenic Psychological Society, 2019)
The explanatory coexistence of scientific and supernatural explanations in the same mind challenges the most influential theories of knowledge acquisition in psychology. It shows that although individuals acquire the scientific theories, the supernatural explanations are also used as causal explanatory frameworks even by experts. The present review and meta-analysis aimed to explore the factors that could influence the coexistence of supernatural and scientific explanatory frameworks in the concepts of the origins of life, illness and death/afterlife. On the basis of 35 identified articles (45 studies) that have been published between 1985 and 2016 and that examined both scientific and supernatural explanations within these concepts, the impact of age, religiousness, scientific expertise, cultural background and contextual factors was explored. Results suggest that although religiousness, cultural background, and contextual information have a large effect on the concepts of death/afterlife, illness and the origins of life respectively, the magnitude of the average effect depends on the concept.